PENGARUH DIMENSI KUALITAS PELAYANAN JASA TERHADAP KEPUASAN NASABAH - Rully Tri Indriastuti, Untung Sriwidodo & (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2010)
ABSTRACT The analysis results which could be reported are: (1) The questionnaire of all variables are valid and the variability’s result is reliable, (2) The result of classical assumption test show that the model is no multicolinierity, no heteroskedasticity, no autocorrelation and the residual is normal. Results of t test indicate that (1) the reliability dimension of service quality has a significantly positive effect on customer satisfaction, thus supporting hypothesis 1; (2) the responsiveness dimension of service quality has a significantly positive effect on customer satisfaction, thus supporting hypothesis 2; (3) the assurance dimension of service quality has a significantly positive effect on customer satisfaction, thus supporting hypothesis 3; (4) the empathy dimension of service quality has a significantly positive effect on customer satisfaction, thus supporting hypothesis 4; (5) the tangibles dimension of service quality has a significantly positive effect on customer satisfaction, thus supporting hypothesis 5. (6) Dimension’s of service quality (reliability, responsiveness ,assurance, empathy, dan tangibles) has a significantly effect in a simultaneous on customer satisfaction, thus supporting hypothesis 6; (7) the responsiveness of service quality has most dominant influence to customer satisfaction, thus supporting hypothesis 6. Coefficient determination test is Adjusted R2 = 0,385; it means that the influence of reliability, responsiveness, assurance, empathy, dan tangibles variables are explain as 38.5% to customer satisfaction only, further more influenced by the other variables. Keywords:    service quality, reliability, responsiveness, assurance, empathy, and tangibles, consumer satisfaction.